EFFECT OF FOLIC ACID SUPPLEMENTATION ON APPETITE IMPROVEMENT IN PRE-SCHOOL CHILDREN (Journal of Medical & Health Sciences Review, 2025)
Objective: To observe the effect of folic acid supplementation on appetite improvement in pre-school childrenStudy Design: Randomized Control TrialPlace and Duration of Study: Department of Pediatric, KRL Hospital, Rawalpindi, Pakistan, November 2024 to june 2025.Methodology: Fifty children of age 3-5 years with who were below the 50th percentile on the growth chart enrolled. Children were divided in to two groups A and B, each consisting of 22 children. Group A patients were to receive folic acid in a dose of 200µg/day while Group B was given a placebo in the form of a glucose capsule. Variables including number of meals, Child Eating Behavior Questionnaire (CEBQ) score, weight, growth percentile and hemoglobin levels were checked at baseline and at 3-month for improvement in these parameters. Means were compared between both groups with a significant p-value of ≤ 0.05.Results: Total fifty children included in the trial with mean age of 45.74±7.73 months including 21 (42%) girls and 29 (58%) boys having mean growth percentile of 28.14±7.8 and BMI of 15.78±0.33 kg/m2 at baseline. The studied variables such as appetite, BMI, growth percentile, CEBQ score and hemoglobin when compared across groups showed no significant differences between the groups at the end of 3 months. However, intragroup comparison showed significant improvement in these whether the patient took folic acid or placebo.Conclusion: Folic acid appears to improve appetite but insignificantly differ from the effects of other dietary measure and lifestyle modifications.